2015
DOI: 10.3389/fpsyg.2015.00814
|View full text |Cite
|
Sign up to set email alerts
|

Musical hallucinations: review of treatment effects

Abstract: Background: Despite an increased scientific interest in musical hallucinations over the past 25 years, treatment protocols are still lacking. This may well be due to the fact that musical hallucinations have multiple causes, and that published cases are relatively rare.Objective: To review the effects of published treatment methods for musical hallucinations.Methods: A literature search yielded 175 articles discussing a total number of 516 cases, of which 147 articles discussed treatment in 276 individuals. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 135 publications
2
49
0
10
Order By: Relevance
“…4 The physiological basis for MHs involves diverse mechanisms, including "release" from normal sensory or inhibitory inputs as well as stimulation during seizures. 5 Functional or structural disorders in diverse cortical and subcortical areas can produce MHs. 6 However, in some cases, neither a localized lesion nor a functional disorder can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…4 The physiological basis for MHs involves diverse mechanisms, including "release" from normal sensory or inhibitory inputs as well as stimulation during seizures. 5 Functional or structural disorders in diverse cortical and subcortical areas can produce MHs. 6 However, in some cases, neither a localized lesion nor a functional disorder can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Older women with auditory difficulties also report hearing familiar songs. Despite a view of limited therapeutic effects of antipsychotics for this condition, two patients with MH, reported herein, were successfully treated with quetiapine. The patients gave informed consent to publish this letter and their anonymity has been preserved.…”
mentioning
confidence: 76%
“…As previously mentioned, the study performed by Coebergh et al stratified subgroups of patients based on medical and psychiatric illness and postulated that in the psychiatric groups it appeared that the type of disorder was the most important guide as to the choice of treatment. 12 In our cases the most closely associated symptom was psychosis, thereby the choice to utilize atypical antipsychotics was made for this reason.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings showed that while the two previously mentioned classes of medications do have higher efficacy than most, other classes such as antipsychotics may be more beneficial in patients exhibiting acute psychotic symptoms. 12 Our study builds on the current literature by presenting two complex patients who were successfully treated with aripiprazole and quetiapine for this reason.…”
Section: Introductionmentioning
confidence: 99%